Konsep Tanzîl dalam Perspektif Arkoun dan Zarqani - Anwar Ma’rufi (Universitas Darussalam Gontor, 2016)
Arkoun expressly states, that when revelation was sent down by God, it has been affected by the historical and social reality of Arab culture. Differing from the majority of ’Ulama, Zarqani, he regarded that the composition of word and meaning are solely from God and not contaminated by angels, human and especially culture. This article will compare the two figures and their thoughts, Arkoun from among liberal Muslims and Zarqani representing mojority of ‘Ulama on the concept of tanzîl of the Qur’an. By using the compare and contrast method, considered to it can be found, that the deconstuction of the meaning of tanzîl by Arkoun were considered to stultify the interpretation of the Qur’an.